Prevalence and risk factors of migraine headache among university students: A cross-sectional study in Lebanon - Hatem, Georges; Mosleh, Reva; Goossens, Mathijs; Khachman, Dalia; Al-Hajje, Amal; Awada, Sanaa (Headache Medicine, 2022)
Background Migraine constitutes a major public health concern since it negatively affects both the quality of life and the productivity of patients. Migraine among students can cause impaired academic performance and limit their daily activities. Objective This study aims to assess the prevalence of migraine among university students using the ID Migraine screening tool and to evaluate risk factors associated with migraine. Methods A cross-sectional study was performed over a period of six months targeting 1144 university students recruited from the different faculties. Results Migraine was suggested in 35.8% of subjects based on ID-Migraine. Migraine prevalence was significantly higher among women (42% versus 23.3% of men). After adjusting for covariates, women, daily coffee consumption, having unorganized meals, eating fast food and fasting were the main predictors of migraine. Almost 41% of migraine students had a family history of migraine and only 26.7% sought medical help. Interestingly, most of the migraine students (84.8%) took headache medications without referring them to their doctor. Conclusion Recognizing headache risk factors among migraine students and adopting lifestyle changes accordingly can be an effective strategy to prevent the chronification of the attacks, decrease headache frequency and improve patients’ quality of life.